PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT POS INDONESIA KOTA KUDUS JAWA TENGAH - Satria Avianda Nurcahyo; Teguh Harso Widagdo; Ahmad Ali; Sudiyono (Journal of Social Sustainability Management, 2023)
The purpose of this study was to determine the effect of the variable Competence, Career Development, and Organizational Commitment on employee performance improvement. The data used in this study were primary data in the form of distributing questionnaires as many as 100 respondents to PT Pos Indonesia Kudus employees. The sampling technique used in this study was purposive sampling. The test of this study used path analysis and to test the effect of the intervening variables the sobel test was used. The results showed that (1) competence has a positive effect on organizational commitment. (2) career development has a positive effect on organizational commitment. (3) competence has a positive effect on employee performance. (4) career development has a positive effect on employee performance. (5 organizational commitment has a positive effect on employee performance. Regarding the variable organizational commitment is not able to become an intervening variable, an employee is expected to work actively and help each other so that it can increase organizational commitment. Then by making employees have a strong sense of organizational commitment and grow slowly by creating a work atmosphere like a family, by implementing this family management, employees will feel comfortable, feel more psychologically cared for, and feel a family bond